Autotext Emoticons as A Message Carrier in Blackberry - Fadia Anugrah Tuesa (Universitas Pendidikan Indonesia (UPI), 2014)
This paper entitled “Autotext Emoticon as Message Carrier in Blackberry” is aimed to investigate the meaning and the function of the Eastern emoticons used in Blackberry Messenger and to discover the differences between male and female in using emoticons. The study is qualitative which utilizes Eco’s (1994) Hermetic drift theory. The main data are 10 emoticons which were used in ten different conversations in Blackberry messenger. There are 15 conversations which consist of five conversations between male and female, five conversations between female and female, and five conversations between male and male. The study revealed that the emoticons function to i) represent feelings, 2) strengthen messages, and 3) joke around. It also revealed that females become more expressive than males in using emoticons in a conversation between female and female. To some extent, males are the opposite, males become less expressive in using emoticons between male and male. However, males are like females in expressing their feelings so that they appear as expressive as females in the conversation between female and male.Keywords: Semiotic, Eastern Emoticons, Autotext Emoticons, Gender contribution, Blackberry